Analysis of the applicability of correlation and regression models to assess the factors of aviation fuel supply to the remote Arctic regions of the Far North - V. P. Gorbunov; V. M. Samoylenko; S. V. Kuznetsov; A. M. Struchkova (Научный вестник МГТУ ГА, 2023)
Air transport for the Far East and the Far North is a strategically important mode of transport for most of its part and especially in the Arctic regions. Air transportation plays the most important social and economic role, providing the fastest connection with the rest of Russia and vital transport accessibility of the population of a strategically important region of the Russian Federation. Air transport plays a special role in the largest region of the Russian Federation, the Republic of Sakha (Yakutia), which remains the most isolated and inaccessible region of the country. In the republic, aviation is the only year-round means of transport communication on 85% of the territory. At the same time, the most important factor affecting the year-round provision of transport accessibility for the vast majority of airports in the republic, and especially in the Arctic zone, is the delivery of the required amount of aviation fuel, provided that its consumer properties are preserved. The unique and complex scheme of aviation fuel delivery to the Arctic and remote areas of Yakutia, with up to nine transshipments, leads to the loss of some important parameters of aviation fuel, such as electrical conductivity, and forces airlines flying to the Arctic and remote areas of Yakutia to look for more optimal logistics ways of delivery, storage, ensuring the safety of properties and parameters of aviation fuel. Another factor that directly affects the year-round provision of transport accessibility of the population is the cost of jet fuel, which is about 30 % of the costs of base airlines, such as Yakutia Airlines, where at the base airport Yakutsk the cost of jet fuel in 2021 reached 88 thousand rubles per ton, provided refueling in the wing, with an average value for all airports Russia has about 58 thousand rubles per ton. At the same time, the cost of jet fuel at Arctic airports has approached or has already reached 100 thousand per ton. In order, to find solutions, the authors of this article used a research methodology based on factor analysis using the apparatus of economic and mathematical modeling of the problem of jet fuel delivery due to optimization of the logistics scheme of delivery to remote regions of the Arctic zone. By applying capability assessments correlation and regression analysis, estimation factors for the jet fuel supply chain optimization by optimizing the logistics scheme were carried out. As a result of the research and along with the proposed solutions of practical, technological and economic nature, a regression model is considered on the basis of which the most optimal options for the development of fuel supply of the Republic of Yakutia for air transport in the coming period can be suggested.